Why Do Some Family Businesses Out–Compete? Governance, Long–Term Orientations, and Sustainable Capability - Le Breton–Miller, Isabelle; Miller, Danny (Entrepreneurship Theory and Practice, 2006)
This article seeks to link the domains of corporate governance, investment policies, competitive asymmetries, and sustainable capabilities. Conditions such as concentrated ownership, lengthy tenures, and profound business expertise give some family–controlled business (FCB) owners the discretion, incentive, knowledge, and ultimately, the resources to invest deeply in the future of the firm. These long–term investments accrue from particular governance conditions and engender competitive asymmetries—organizational qualities that are hard for other firms to copy, and thus, if tied to the value chain, create capabilities that are sustainable. Investments in staff and training, e.g., create tacit knowledge and preserve it within the firm. Investments in enduring relationships with partners enhance access to resources and free firms to focus on core competencies. And devotion to a compelling mission dedicates most of these investments to a core competency. When such investments are farsighted, orchestrated, and ongoing, capabilities will tend to evolve in a cumulative trajectory, making them doubly hard to imitate and thereby extending competitive advantage. Arguments are supported by making reference to the literature on corporate governance and agency theory and to emerging research on FCBs.